Antiflammin-2 Activates the Human Formyl-Peptide Receptor Like 1. (2006) - Kamal, Ahmad M.; Hayhoe, Richard P.G.; Paramasivam, Anbalakan; Cooper, Dianne; Flower, Roderick J.; Solito, Egle; Perretti, Mauro
Abstract : The anti-inflammatory actions of the nonapeptide antiflammin-2, identified by homology with uteroglobin and annexin-A1 sequences, have been described in some detail, yet its mechanisms of action remain elusive. Since recent data indicate an involvement of the formyl peptide receptor (FPR)-like 1 (or FPRL-1) in the effects of annexin-A1, we have tested here the effect of antiflammin-2 with respect to this receptor family. Using HEK-293 cells expressing either human FPR and FPRL-1, and an annexin-A1 peptide as tracer ([ 125 I-Tyr]-Ac2-26), we found that antiflammin-2 competed for binding only at FPRL-1, and not FPR, with an approximate EC50 of 1 μM. In line with data produced for the full-length protein, genuine receptor activation by antiflammin-2 was confirmed by rapid phosphorylation of extracellular-regulated kinase 1 and 2. Finally, study of the neutrophil interaction with activated endothelium under flow demonstrated an inhibitory effect of antiflammin-2, thus providing functional support to a role for the antiflammin-2/FPRL-1 anti-inflammatory axis.